Effective Teaching Methods: The Teacher’s Role in Selection and their Impact on the Educational Process - Hawaa Hadi, Asst. Lect. (lark, 2025)
This research paper explores the critical role of teachers in selecting and implementing effective teaching methods and their subsequent impact on the educational process. It highlights the importance of teachers’ pedagogical knowledge and understanding of their students’ diverse learning needs in choosing appropriate instructional approaches. The study investigates the relationship between various teaching methods, such as active learning, collaborative learning, and differentiated instruction, and their effectiveness in fostering student engagement, motivation, and academic achievement. It also examines the challenges teachers face in adapting their teaching practices to meet the evolving demands of the 21st-century learning environment. By analyzing the impact of effective teaching methods on student learning outcomes, this research aims to provide valuable insights for educators, policymakers, and curriculum developers in creating a more impactful and student-centered educational experience.